عملية اتخاذ القرار وعلاقتها بالالتزام الوظيفي لدى أعضاء فريق العمل دراسة ميدانية بمؤسسة كوندور إلكترونيكس "عنتر ترّاد " - عمير, سهيلة; ضيف, الأزهر (جامعة الوادي - University of Eloued, 2022)
انطلاقا من أن فريق العمل يتيح فرصة لإبراز أفضل المواهب والمهارات لدى الفرد العامل، تميل الإدارة الحديثة إلى التحرر من القواعد والنظم والإجراءات الجامدة، من خلال دمج القدرات والإمكانيات الفردية في أنشطة وأعمال ذات طابع تشاركي تعاوني، من أجل تحقيق أفضل النتائج وإشباع الحاجات النفسية والاجتماعية للفرد العامل. من هنا هدفت هذه الدراسة إلى توضح العلاقة بين عملية اتخاذ القرارات والالتزام الوظيفي لدى أعضاء فريق العمل بالمؤسسة الصناعية الجزائرية، وذلك من خلال توضيح ما يلي:  العلاقة بين المشاركة في اتخاذ القرارات وانضباط الفرد العامل ضمن فريق العمل.  العلاقة بين لامركزية اتخاذ القرارات بتوجيه جهود الأفراد العاملين ضمن فريق العمل لتحقيق الأهداف المرجوة.  العلاقة بين تفويض الصلاحيات لأعضاء الفريق ومستويات الرضا الوظيفي. الكلمات المفتاحية: اتخاذ القرار؛ الالتزام الوظيفي؛ فريق العمل. Abstract: The team work provides an apportunity to express the best abilities and skills of factory worker The modernes management trying to deregulate from rigid rules regulations and procedures by employee treating on taking decision Integrate the capabilities and experiences of individuals into participatory activities and tasks for the best results And satisfaye the psychological and social needs for the individual worker. From here the purpose of this study is clear the relationship between the decision-making process and the job commitment of the teamwork members in industrial enterprise Through clarify the following:  The relation between taking decision and discipline of employed into teamwork  The relation between décentralisation of taking decision and steering individual workers efforts into teamwork to achieving expected goals  The relation between delegation of authority for the team members and the levels of job satisfaction
The decision-making process and it's relation with job commitment in teamwork members Field research at condors electronics "antar trade " company
مقال
Keywords: اتخاذ القرار، الالتزام الوظيفي، فريق العمل.; decision making, job commitment , teamwork.